Analysis Of Usability Level PeduliLindungi Application - Essy Malays Sari Sakti; Diah Pramestari; Dian Gustina; Susi Wagiyati P; Yunita Sari; Nursina Nursina; Purwanti Purwanti; Boy Firmansyah; Nur Ismawati; Merry Nancylia (Research Synergy Foundation, 2022)
In order to fight the spread of the coronavirus (Covid 19) in Indonesia, the Ministry of Communication and Information, in partnership with other relevant ministries and organizations, is developing the PeduliLindungi application, which serves as an information tool and tracks the movement of Indonesians who may be infected with the virus. The purpose of this study was to examine the community's level of knowledge and difficulty in utilizing the PeduliLindungi application. This study evaluates the usability of the PeduliLindungi application in five categories: learnability, efficiency, memorability, error, and satisfaction are all important factors to consider. This research is quantitative descriptive. In this study, data was collected using an online questionnaire administered to Indonesians using Google Forms, with the variable measurement scale referring to the likert scale. The results showed that the usability level was said to be good with an average score of around 72.85 and a satisfaction percentage of 79.3% so that it can be said that the PeduliLindungi application is user-friendly, with an indication that the application features are easy to use, understand and use, efficient in operation, coloring is comfortable to see, but the error rate is below the average value, this is because the network is unstable and users are not familiar with this application. The limitation of this study is only to calculate the usability level of the PeduliLindungi application to determine the comfort in using the application.